Enhancing the prebiotic properties of malted barley - Persson, Jenny (My University, 2015)
Prebiotics can improve health indirectly by promoting probiotic bacteria in the gut and production of beneficial metabolites by the gut microbiota. In this project the possibility to enhance the potential prebiotic properties of malted barley was explored. The aim was to find yeast strains with high potential to modify the polysaccharide composition, in particular the β-glucan profile, in malted barley and investigate if fermentation of barley malt materials by these yeast strains can promote growth of probiotic bifidobacteria and the production of organic acids. Firstly, the β-glucan content in Brewers’ Spent Grain was determined. Thereafter, yeasts were screened for production of β-glucanase enzyme. The growth of strains showing this ability was studied in the malt materials in order to select optimal strains to be used in further experiments with bifidobacteria. Pichia butronii TY01 and Pichia kudriavzevii TY3 were found to be most suitable for fermentation of the malt materials based on β-glucanase activity and highest increase in cell numbers during growth in malt materials. The potential impact of the fermented malt materials on gut health was evaluated by analysing growth of Bifidobacterium bifidum and Bifidobacterium breve in malt-based media and the subsequent production of organic acids, in particular lactic acid. Indications of increased growth of Bifidobacterium in fermented malt was observed. Furthermore, a higher concentrations of lactic- and acetic acid was found in fermented malt compared to unfermented samples. Brewers’ Spent Grain generated lower organic acid concentrations compared to malted barley, possibly due to differences in the β-glucan content. In conclusion, this study showed increased prebiotic properties of barley malt materials fermented by β-glucanase producing yeast strains compared to unfermented materials.
Keywords: Livsvetenskaper; Biokemi och molekylärbiologi; Life Science; Biochemistry and Molecular Biology